Lingkungan Pendidikan Islam Dalam Perspektif Al Qur’an - Waheeda bt Abdul Rahman (Al Ashriyyah, 2020)
Human caliph, has a big and important responsibility in protecting and preserving everything on this earth. To be able to create humans as caliphs or leaders who are fathonah, mandate, siddiq for tabligh, of course it requires knowledge and education, especially those based on the Qur'an and Hadiths, it must be applied from an early age.Feathered birds gather together. Birds with the same feathers will gather together. Shows how the importance of the environment affects a human being. Nature versus nurture is a fun thing that is often done by psychologists, educationists, sociologists and anyone with knowledge related to humans. Will a human being know more about his seeds or heredity, namely nature, or care, from the environment, education, family upbringing and government? The two terms above indicate the role that the environment affects on an individual's personality, especially the educational environment.The Islamic education environment in the perspective of the Qur'an can be a solution to form perfect human resources, which are beneficial to Islam and the nation. Like the adage, "Baldatun toyyibatun wa robun ghofur" in a good country, Allah SWT. will give forgiveness. Human resources formed from a good environment and country will be the basis for forgiveness and compassion from Allah SWT.In order to understand more clearly about what and how the nature of the educational environment is extracted from the verses of the al-Qur'an, it is necessary to conduct an in-depth study of the educational environment according to the al-Qur'an.